Exome Sequencing Identifies a Novel Nonsense Mutation of MYO6 as the Cause of Deafness in a Brazilian Family. (17th October 2017) - Sampaio‐Silva, Juliana; Batissoco, Ana Carla; Jesus‐Santos, Rafaela; Abath‐Neto, Osório; Scarpelli, Luciano Cesar; Nishimura, Patricia Yoshie; Galindo, Layla Testa; Bento, Ricardo Ferreira; Oiticica, Jeanne; Lezirovitz, Karina
Summary: We investigated 313 unrelated subjects who presented with hearing loss to identify the novel genetic causes of this condition in Brazil. Causative GJB2 / GJB6 mutations were found in 12.7% of the patients. Among the familial cases (100/313), four were selected for exome sequencing. In one case, two novel heterozygous variants were found and were predicted to be pathogenic based on bioinformatics tools, that is, p.Ser906* ( MYO6 ) and p.Arg42Cys ( GJB3 ). We confirmed that this nonsense MYO6 mutation segregated with deafness in this family. Only the proband and her unaffected mother exhibited the GJB3 mutation, which is in the same amino acid of a known Erythrokeratodermia variabilis mutation. None of the patients exhibited this skin disease, but the proband exhibited a more severe hearing loss. Hence, the GJB3 mutation was considered to be a variant of uncertain significance. In conclusion, we described a novel nonsense MYO6 mutation that was responsible for the hearing loss in a Brazilian family. This mutation resides in the neck domain of myosin‐VI after the motor domain. Thus, our data give further support for genotype‐phenotype correlations, which state that when the motor domain of the protein is functioning, the hearing loss is milder and has a later onset. The three remaining families without mutations in the known genes suggest that there are still deafness genes to be revealed.